2018
DOI: 10.1556/650.2018.31217
|View full text |Cite
|
Sign up to set email alerts
|

Vérlemezke-mikro-RNS-ek expressziójának változása thrombocytaaktivációval járó betegségekben

Abstract: MicroRNAs (miRNA) are short, non-coding RNAs consisting of 18–25 nucleotides that regulate posttranscriptionally the gene expression involved in the regulation of physiological processes of the cells. Their key role is to modulate the translation of target mRNAs via binding to complementary sequences within the 3’ UTRs of mRNAs resulting in altered protein synthesis or even the degradation of mRNAs. miRNAs are carried not only by cells with nucleus, but also in platelets, red blood cells, and they are present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 57 publications
(77 reference statements)
0
7
0
Order By: Relevance
“…On the other hand, there was an increased expression of microRNA-486 and microRNA-182 in these patients [67]. A similar study carried out by Benz et al, identified important changes in microRNA-233 in patients with sepsis [68]. Other species involved in the molecular and genetic sepsis reactions include microRNA-340, microRNA-324-3p, microRNA-16, microRNA-210, let-7b, microRNA-15b, microRNA-484, microRNA-486-5p, and microRNA-324-3p [69].…”
Section: Microrna Expression In the Case Of Polytrauma Patients Wimentioning
confidence: 95%
See 4 more Smart Citations
“…On the other hand, there was an increased expression of microRNA-486 and microRNA-182 in these patients [67]. A similar study carried out by Benz et al, identified important changes in microRNA-233 in patients with sepsis [68]. Other species involved in the molecular and genetic sepsis reactions include microRNA-340, microRNA-324-3p, microRNA-16, microRNA-210, let-7b, microRNA-15b, microRNA-484, microRNA-486-5p, and microRNA-324-3p [69].…”
Section: Microrna Expression In the Case Of Polytrauma Patients Wimentioning
confidence: 95%
“…In the next step, RNAse III endonuclease, also called Drosha, activates the pri-microRNAs. This reaction is catalyzed by the DiGeorge Syndrome Critical Region 8 (DGCR8) complex, which leads to the formation of pre-microRNAs [15,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,56,57,58,59,60,61,62,63,64,65,66,67,68,69,70,71,72,73,74].…”
Section: Biochemical and Biosynthesis Aspects Of Micrornasmentioning
confidence: 99%
See 3 more Smart Citations